Green synthesis of silver nano-catalyst using ionic liquid and their photocatalytic application to the reduction of p-nitrophenol - Ranjan, Ravi; Gupta, Durga; Shukla, Madhulata (European Journal of Chemistry, 2023)
Ionic liquids (ILs) carrying special properties can act as electronic as well as steric stabilisers by preventing nanoparticle (NP) growth and NP aggregation. The effect of visible light on the catalytic properties of silver nanoparticles is a hot topic of extensive research nowadays. The present report demonstrates the current developments in the green synthesis of silver nanoparticles in ionic liquids and a detailed study of the room-temperature catalytic and photocatalytic reduction of p-nitrophenol (PNP) to p-aminophenol (AP). The Ag nanoparticles (AgNPs) functionalised by ionic liquids are prepared in the 40-140 nm range and are found to be spherical in shape. The photocatalytic properties of these nanocomposites for the reduction of PNP to AP were studied. Photocatalytic degradation of PNP was also analysed by these composite nanostructures. The plasmonic photocatalytic properties of the synthesised AgNPs revealed activity significantly higher than that of the room-temperature catalysis. Density functional theory calculations showed that strong interactions exist between nanoclusters and ILs. Natural bond orbital analysis showed that IL also activates the nanoparticles for further photocatalytic reduction by transferring electron transfer from the donor (IL) to the acceptor (Ag cluster) and activating the silver NPs for further catalytic reaction. Photocatalytic degradation of PNP (reduction of PNP to AP) using NP in the absence of light follows first-order kinetics, whereas in the presence of light it follows zero-order reaction kinetics.